The Influence of Dividend Policy, Deferred Tax Burden and Company Size on Profit Management - Wulan Lestari; Nur Asmilia (Journal of Community Service and Rural Development, 2024)
This study aims to obtain empirical evidence of the effect of dividend policy, deferred tax expense and company size simultaneously on earnings management. Obtain empirical evidence of the effect of dividend policy on earnings management. Obtain empirical evidence of the effect of deferred tax expense on earnings management. Obtain empirical evidence of the effect of company size on earnings management The population in this study are food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022, totaling 126 companies. Sampling was carried out using purposive sampling method and obtained a sample of 9 companies. So that the amount of data processed with an observation period of 5 years is 45 data. This type of research is quantitative and uses secondary data. Data collection techniques are carried out by documentation and literature study. The data analysis technique used is descriptive statistical analysis, classical assumption test, panel data regression analysis and hypothesis testing using the help of Eviews 12. The results showed dividend policy, deferredtax expense and company size simultaneously have a significant effect on earnings management. Dividend policy has a significant effect on earnings management. Deferred tax expense has no effect on earnings management and company size has no significant effect on earnings management.